Hungry for ecstasy trauma, the brain, and the influence of the sixties - Farber, Sharon Klayman (Jason Aronson, 2013)
"Hungry for Ecstasy: Trauma, The Brain, and the Influence of the Sixties by Sharon Klayman Farber explores the hunger for ecstatic experience that can lead people down the road to self-destruction. In an attempt to help mental health professionals and concerned individuals understand and identify the phenomenon and ultimately intervene with patients, friends, and loved ones, Farber discusses the different paths taken on the road to ecstatic states. Hungry for Ecstasy explores not only the neuroscientific processes involved but also the influence of the sixties in driving people to seek these states. Finally, Farber draws from her own personal and professional experience to advise others how to intervene on behalf of the person whose behavior puts his or her life at risk"--Provided by publisher.